Teamwork: A Systematic Review of Implications From Psychosocial Constructs for Research and Practice in the Performance of Ultimate Frisbee Games - Amoroso, José Pedro (2021)
Introduction: Ultimate Frisbee (UF) is a non-contact, challenging, and self-promoted team sport. Some factors such as the game environment and rules seem to influence athletes’ behavior. Goals: Provide a robust systematic review (SR) of the psychological domains associated with UF.